THE ROLE OF MUSIC TRAINING IN THE COMPREHENSIVE DEVELOPMENT OF SCHOOLCHILDREN (American Journal of Pedagogical and Educational Research, 2025)
Of all the arts, it is music that most directly influences human perception, because it has a strong influence on the subconscious level not only on a person’s feelings, but also on his mind. Music reflects a person’s moods and experiences, his emotional world. The subtlety, strength and diversity of mental states revealed in music constitute its main content.